ANALISIS PENGAMBILAN KEPUTUSAN BERBASIS FAKTA DALAM MEMBANGUN BUDAYA SEKOLAH DI SMAN 1 BENTIAN BESAR - Intan Beauty Kusnukiandany; Friska Umi Puspita Sari; Irmawati; Azainil; Laili Komariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the era of digital transformation, schools are required to no longer rely solely on intuition in management, but instead implement decision-making based on data, facts, and empirical evidence through a data-driven decision-making (DDDM) approach. This approach has been proven to improve learning quality, program effectiveness, and build a reflective school culture oriented towards continuous improvement. However, in Indonesia, significant challenges remain, as evidenced by the results of the 2022 Programme for International Student Assessment, which showed that student literacy, mathematics, and science outcomes remain below the OECD average. This situation emphasizes the need for schools to utilize academic data, student behavior, and program evaluations as a basis for objective and targeted policies. In practice, many schools still face constraints due to low data literacy, technological limitations, and suboptimal leadership support. This impacts policy effectiveness and the formation of a less adaptive school culture. In the local context, SMAN 1 Bentian Besar faces geographical challenges and limited resources, making fact-based decisions a crucial strategy for determining priorities, optimizing potential, and building a collaborative, transparent, and quality-oriented school culture. Therefore, this research is important to analyze how fact-based decision-making is implemented and its contribution to building an effective and sustainable school culture.